Analysis of Teacher Performance Assessment in Elementary School - Yani, Efrida; Sari, Siti Mayang; Mukhlisuddin, Mukhlisuddin (IJBLE Scientific Publications Community Inc., 2024)
Teacher performance assessment is the process of giving grades to teacher performance which includes aspects of leadership, honesty, loyalty, dedication and teacher participation in institutional or group organization activities. Teacher performance assessment is the process of giving grades to teacher performance based on elements of the teacher's main activities, which aims to develop the teacher's rank, professionalism and position. The aim of this research is to determine the competencies that can be used to evaluate the performance of elementary school teachers, the indicators needed to carry out the main functions and duties of elementary school teachers, research on teacher performance, and the benefits of teacher evaluation. show. This research uses library research methods, namely research carried out by collecting data from various library sources, such as books, journals, articles, and so on. Teacher Competency Standards consist of four main competencies, namely pedagogical, personality, social and professional competencies. These four competencies are interrelated and integrated in teacher performance. Teachers' teaching skills are seen from several indicators, namely questioning skills, reinforcement skills, variation skills, explanation skills, lesson opening and closing skills, small group discussion guiding skills, class management skills, and individual learning skills. In conclusion, teacher performance has certain criteria that can be seen and measured based on specifications or competency criteria that every teacher must have.